Analysis of Customer on Boarding Implementation in Supporting Green Banking at BMI KCP Ponorogo - Nugroho, Dika Yulianto Bagus; Anhar, Fibrianis Puspita (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: Banks are responding to environmental concerns by adopting green banking practices. Financial institutions such as Sharia banking can contribute to sustainable development that meets current and future needs. Furthermore, the banking industry can play a role in balancing the economy and the environment. The customer onboarding service facilitates quick and precise transactions. Research Methods: This research analyzes the implementation of the customer onboarding service at Bank Muamalat Indonesia Ponorogo Head Office (BMI KCP Ponorogo) in support of green banking. This research is descriptive qualitative research. The primary data source used includes interviews, documentation, and observation. Results: The research findings indicate that customer onboarding at BMI KCP Ponorogo supports green banking through online transactions. BMI KCP Ponorogo implements customer onboarding as its commitment to conducting healthy operational activities in line with the principles of green banking and the requirements of Bank Indonesia. Conclusion: Customers benefit from customer onboarding as it makes the transaction process more effective and efficient, providing flexible access while supporting the green economy for sustainable development.